2017
DOI: 10.4103/0259-1162.186590
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of four subdoses of dextroketamine to reduce pain during posterior brachial plexus block: A randomized double blind study

Abstract: Background:The needle puncture produces discomfort during regional anesthesia. Sedation and local anesthesia are used to promote analgesia and amnesia. The main objective of this study was to compare the efficacy of four subanesthetic doses of dextroketamine for pain relief during brachial plexus block via the posterior approach.Materials and Methods:Patients American Society of Anesthesiology I and II programed for elective surgery under brachial plexus block were distributed at randomized into four groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…11 Our group has long experience with the technique using nerve stimulation with several published articles. 5,8 This fact was confirmed in this series of 50 patients with 80% of the first attempts to be successful in locating the brachial plexus, similar results and those of other authors. 11 In another article with catheter insertion through the needle, neck pain was caused by penetrating the extensor paraspinal muscles of the neck.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…11 Our group has long experience with the technique using nerve stimulation with several published articles. 5,8 This fact was confirmed in this series of 50 patients with 80% of the first attempts to be successful in locating the brachial plexus, similar results and those of other authors. 11 In another article with catheter insertion through the needle, neck pain was caused by penetrating the extensor paraspinal muscles of the neck.…”
Section: Discussionsupporting
confidence: 87%
“…All patients were initially sedated with intravenous midazolam 1 mg and before placement in the puncture position for blockade with 0.1μg/kg dextroketamine. 8 Immediately after placement in the sitting position the puncture site was identified and marked. With aseptic condition, the plexus block was performed with a needle A100 needle gauge 21G with a cutting bevel of 30˚ with 1 mL of 1% lidocaine infiltration, coupled to a NE.…”
mentioning
confidence: 99%
“…Recent studies have found that a sub-anesthetic dose of ketamine can significantly reduce the psychiatric symptoms induced by ketamine. The sub-anesthetic dose of ketamine is defined as intravenous ketamine ≤ 0.5 mg kg −1 , usually 0.1–0.5 mg kg −1 ( Imbellon et al, 2017 ). Studies have also shown that 0.3 mg kg −1 ketamine used in painless induced abortion anesthesia did not cause delirium, sleep talk, and other mental symptoms ( Schwenk et al, 2018 ), so we selected three different doses of ketamine in this study for clinical observation, in order to optimize the lowest effective treatment dose.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Esketamine is twice as potent as racemic ketamine. Similarly, to the study by Imbellon et al, 16 we used a single IV injection of 0.25 mg/kg of esketamine as a subanesthetic dose.…”
Section: Discussionmentioning
confidence: 99%